Profil Penggunaan Obat Antiinflamasi Nonstreoid di Indonesia - Soleha, Maratu; Isnawati, Ani; Fitri, Nyoman; Adelina, Rosa; Soblia, Hamim Tsalis; Winarsih, Winarsih (Jurnal Kefarmasian Indonesia, 2018)
Nonsteroid Antiinflamation Drugs (NSAIDs) are available in drug store and be bought as a pain relief. Basic Health Research (Riskesdas) 2013 study the medicines stored in household. Basic Health Research (Riskesdas) 2013 was held in 33 provinces and 497 districts in Indonesia. The research encompasses 300.000 households in 12.000 blocks cencus. The participants were designated households and its member of the family. The study were interviewing the participants to obtain data of all drugs that are stored and used, including traditional medicines. The data including the brand, indication, the provenance (prescribed or unprescribed by doctor), the storage period and also observe drug condition. This study was further analysis of subset data in block IV of Riskesdas 2013 in households. The data were classified by its mechanism and its structure. The result showed that East Java was the highest user of AINS drugs was (15%). Non selectif COX-2 drug and partial selectif COX-2 was 38,3% bought from drug store and 14,4% from drug store. For rheumatism treatment was all used for more than a month. Widely use of NSAIDs as a pain relief indicated the necessity of a proper medicine use information to avoid side effect of NSAID drug.